An X-band beam-scanning reflectarray antenna stimulated using a spoof surface plasmon polaritons based low profile endfire MIMO antenna - Jatav R.; Mali R.; Rathore P.S.; Meshram M.K. (My University, 2025)
A single-layer, low-profile beam scanning reflectarray (RA) fed by a spoof surface plasmon polaritons (SSPPs) based endfire MIMO antenna is proposed in this manuscript. The RA is based on a variable elliptical-shaped unit cell designed at 10.4 GHz. The unit cell has a low insertion loss of 2.3 dB and a reflection phase of 315.2°in the working frequency band from 9.52–11.23 GHz. The SSPPs based endfire MIMO antenna is used to mitigate the aperture blockage, achieve high isolation between the feed elements, and accomplish the continuous one-dimensional (1-D) beam scanning of ± 8°from the broadside. The maximum realized gain of the proposed reflectarray in the broadside direction is 22.6 dBi with a 3-dB beamwidth of 5.7°. The minimal beam switching loss is in the other direction, and the realized gain is 22.4 dBi with a 3-dB beamwidth of 5.8°. The 3-dB gain bandwidth (GBW) of 9.7 % of the proposed RA benefits nano-satellite applications. The fabricated prototype measurements in an anechoic chamber environment verify the simulated results. © 2024 Elsevier GmbH